Prevalence of and Factors Associated With Nutritional Supplement Use Among Older Chinese Adults: A Nationwide Cross-Sectional Study in China - Wanyue Dong; Zhonghe Sun; Ruhai Bai (Frontiers Media S.A., 2022)
ObjectiveThis study identified the prevalence of nutritional supplement (NS) use among older Chinese adults and explored the factors associated with NS use in this population.MethodsWe used data from 11,089 Chinese men and women aged ≥ 65 years from the 2018 Chinese Longitudinal Healthy Longevity Survey. The chi-square test was used to examine the differences in demographics, health status and lifestyles at different levels. Multivariate logistic regression was used to assess the association between NS use and demographic and lifestyle characteristics.ResultsTwelve percent of Chinese adults aged 65 years and above used NS. In terms of the type of supplement used, the most commonly used was calcium (8.49%), followed by protein (2.73%) and multivitamins (2.40%). In terms of demographic characteristics, women, older people, urban residents with other marital status, higher educational level, better living conditions and better lifestyle habits showed a greater use of some kinds of NS to varying degrees. Factors associated with the use of any NS included female gender [OR = 1.71, 95% confidence intervals (95% CI): 1.09-1.44], age 85-94 (OR = 1.30, 95% CI: 1.08-1.58), urban household registration (hukou) (OR = 1.25, 95% CI:1.46-2.00), higher education (primary school and middle school: OR = 1.32, 95% CI:1.14-1.52; high school and above: OR = 1.56, 95% CI:1.25-1.94), average and poor living standard (average: OR = 0.64, 95% CI:0.56-0.73; poor: OR = 0.42, 95% CI:0.32-0.55), poor health status (OR = 1.36, 95% CI:1.13-1.63), former smoking (OR = 1.33, 95% CI:1.11-1.60), and having exercise habits (former exercise: OR = 2.24, 95% CI:1.83-2.74; current exercise: OR = 2.28, 95% CI:2.00-2.61). Women reported taking 2-3 kinds of NSs, and more than 50% of NS users reported taking supplements often.ConclusionThis study provides information on the current prevalence of NS use among older Chinese adults, and it clarifies the association of NS use with demographic, lifestyle and other factors. Providing scientifically based health guidance on NS use for older people is crucial to promoting their health.